Determinants of tuberculosis health service utilization in primary healthcare facilities in Perbaungan, North Sumatra, Indonesia - Ismail, Aniza; Fitra, Nurcholisah; M Zulfakhar Zubir,; Abdul Rahman Bin Ramdzan,; Mohd Ihsanuddin bin Abas, (TROPHICO, 2025)
Indonesia ranks third worldwide in terms of Tuberculosis (TB) cases, after China and India. In 2016, North Sumatera recorded 23,097 TB cases with 5,714 deaths. One of the regencies in this province, Serdang Bedagai particularly in Perbaungan district reported that TB patients with positive smear results did not fully utilize healthcare services or follow the standard treatment protocols provided by primary healthcare centers, according to TB center data from 2016–2017. This study aimed to assess the prevalence and identify factors associated with the utilization of TB health services in primary care. A cross-sectional design was employed with proportionate stratified random sampling among TB patients in Perbaungan. Associations were analyzed using the chi-square test. Inclusion criteria required respondents to be permanent residents aged 20–70 years, both male and female, who agreed to complete the questionnaires. Among 184 respondents, 41.8% showed low utilization of services, while 58.2% demonstrated high utilization. Most respondents had only primary education and were unemployed. The study found significant associations between service utilization and education level, employment status, knowledge, attitudes, and accessibility. In conclusion, nearly half of respondents had low utilization of TB health services in primary health care in Perbaungan, North Sumatera Indonesia.